Enigmas of Health and Disease : How Epidemiology Helps Unravel Scientific Mysteries - ALFREDO MORABIA (Columbia University Press, 2014)
To solve enigmas of health and diseases, epidemiology has become a science that compares groups of people. Group comparisons are a tool to study the health effects of many aspects of human life, including lifestyle factors such as tobacco smoking, lack of exercise, excess caloric intake, oral contraceptive use, alcohol; social conditions such as education, income, occupation, and neighborhood; and environmental exposure such as air pollution. Comparing groups is also at the core of the scientific methods needed to assess the efficacy of medical procedures for prevention and treatment